PERAN ATRIBUT SAFETY RIDING (JAKET KULIT, SARUNG TANGAN, DAN SEPATU) PADA PENGENDARA MOTOR TONG SETAN DI PERTUNJUKAN SEKATEN YOGYAKARTA - Anwar Hidayat; Bayu Aji Suseno (Politeknik ATK Yogyakarta, 2015)
The existence of a melting pot Sekaten in Yogyakarta and all arena shows the main attraction. Performing Tong Satan attractions become one of the main attraction for spectators adrenaline aspect that carried on at the attraction. The problem is the motor driver of Tong Satan does not use a safety riding equipments such as leather gloves, leather jackets, boots and helmets, otherwise the attractions was a dangerous attraction. The aim of this study was to determine the safety aspect of bikers riding on Tong Satan relates to the needs of the show. Ethnographic approach used to obtain the depth of information on the show of Tong Satan. The phenomenon of using safety riding equipments that are not used by the riders because they prefer the interest of the audience who want a dangerous attraction. Symbolic interactionism occured between riders as show performer with the audience, where the dangerous attractions are shown without protective safety riding equipments (leather jackets, shoes, helmets, and gloves), the more boisterous spectators welcome.